Greece : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews macroeconomic developments in the Greek economy in 1995 and early 1996. During that period, the economic recovery gathered strength, driven by a strong pick-up in domestic investment. Although the recovery led to a moderate increase in employment, it did not prevent an increase in the unemployment rate. Inflation continued to decelerate gradually through 1995, but picked up somewhat in the early months of 1996 reflecting in part one-off exogenous factors. These macroeconomic developments, as well as key structural measures adopted in 1995 and early 1996, are described in detail in this paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet